Personal Reading History: Reading Interests Among Pedagogy Students in a Chilean University (2023)
This investigation analyzes 340 reader autobiographies written by prospective language and literature teachers, sourced from eight generations at a Chilean university. This cross-sectional, non-experimental study employed the ‘reader stories’ technique to gather information about reading history and preferences, which were identified based on the frequency of the mentioned titles. Results show that the number of books read in childhood, whether traditional or authored children’s literature, is double the number of titles in the subsequent categories, which consist of stories and novels for adults. It can be affirmed that children’s literature plays a paramount role in biographies. However, diachronic profiles reveal that recent generations report fewer children’s stories than their predecessors, and include more titles from the adult genre that are part of the school canon.